Searching for Utopia, the Challenge of Standardized Medical Nutrition Therapy Prescription in Gestational Diabetes Mellitus Management: A Critical Review - Meloncelli, Nina; Wilkinson, Shelley A.; de Jersey, Susan (Seminars in Reproductive Medicine, 2020)
Gestational diabetes mellitus (GDM) is a common pregnancy disorder and the incidence is increasing worldwide. GDM is associated with adverse maternal outcomes which may be reduced with proper management. Lifestyle modification in the form of medical nutrition therapy and physical activity, as well as self-monitoring of blood glucose levels, is the cornerstone of GDM management. Inevitably, the search for the “ultimate” diet prescription has been ongoing. Identifying the amount and type of carbohydrate to maintain blood glucose levels below targets while balancing the nutritional requirements of pregnancy and achieving gestational weight gain within recommendations is challenging. Recent developments in the area of the gut microbiota and its impact on glycemic response add another layer of complexity to the success of medical nutrition therapy. This review critically explores the challenges to dietary prescription for GDM and why utopia may never be found.
Keywords: gestational diabetes mellitus; medical nutrition therapy; pregnancy; diet